The Effect of Switching from Tenofovir Disoproxil Fumarate (TDF) to Tenofovir Alafenamide (TAF) on Liver Enzymes, Glucose, and Lipid Profile - Squillace N; Ricci E; Menzaghi B; De Socio GV; Passerini S; Martinelli C; Mameli MS; Maggi P; Falasca K; Cordier L; Celesia BM; Salomoni E; et al. (Dove Medical Press, 2020)
Nicola Squillace,1 Elena Ricci,2 Barbara Menzaghi,3 Giuseppe Vittorio De Socio,4 Simone Passerini,5 Canio Martinelli,6 Maria Sabrina Mameli,7 Paolo Maggi,8 Katia Falasca,9 Laura Cordier,5 Benedetto Maurizio Celesia,10 Elena Salomoni,11 Antonio Di Biagio,12 Giovanni Francesco Pellicanò,13 Paolo Bonfanti1 On behalf of the CISAI Study Group1Infectious Diseases Unit ASST-MONZA, San Gerardo Hospital-University of Milano-Bicocca, Monza, Italy; 2“ASIA” Foundation ONLUS, Milan, Italy; 3Unit of Infectious Diseases, ASST della Valle Olona, Busto Arsizio, Italy; 4Department of Internal Medicine 2, Infectious Diseases Unit, “Santa Maria della Misericordia” General Hospital, Perugia, Italy; 5 1st Department of Infectious Diseases, ASST Fatebenefratelli Sacco, Milan, Italy; 6Infectious Diseases Unit, Careggi Hospital, Florence, Italy; 7Unit of Infectious Diseases, Department of Medical, Surgical and Experimental Sciences, University of Sassari, Sassari, Italy; 8University of Campania “Luigi Vanvitelli”, Napoli, Italy; 9Clinic of Infectious Diseases, Department of Medicine and Science of Aging, University “G. d’Annunzio” Chieti-Pescara, Chieti, Italy; 10Unit of Infectious Diseases, University of Catania, ARNAS Garibaldi, Catania, Italy; 11Infectious Diseases Unit, Santa Maria Annunziata Hospital, Usl centro, Florence, Italy; 12Infectious Diseases, San Martino Hospital Genoa, Genoa, Italy; 13Department of Human Pathology of the Adult and the Developmental Age “G. Barresi”, Unit of Infectious Diseases, University of Messina, Messina, ItalyCorrespondence: Nicola SquillaceInfectious Diseases Unit, Azienda Socio Sanitaria Territoriale di MONZA, San Gerardo Hospital-University of Milano-Bicocca, Via Pergolesi 33, Monza 20900, ItalyTel +390392339588Fax +390392339327Email nicolasquillace74@gmail.comObjective: We aimed to investigate the effect of switching from tenofovir disoproxil fumarate (TDF) to tenofovir alafenamide (TAF) on the hepatic safety and metabolic profile.Methods: Consecutive HIV patients, enrolled in the Surveillance Cohort Long-term Toxicity Antiretrovirals/Antivirals (SCOLTA) project, switching from TDF to TAF were included. Changes from baseline (T0) to 6-month follow-up (T1) were evaluated using paired t-test and signed rank test.Results: A total of 190 patients switched from TDF to TAF and had one 6-month follow-up visit. They were 80% male, 74.2% at CDC stage A–B, 93.7% with undetectable HIV-viral load. Mean age was 46.7± 10.7 years, body mass index was 25.0± 3.9 kg/m2, median CD4 cell count was 634 cell/μL (interquartile range [IQR]=439– 900), aspartate aminotransferase (AST) was 23 (IQR=19– 30) IU/L, and alanine aminotransferase (ALT) was 24 (IQR=17– 34) IU/L. At T1, both AST (median=− 1, IQR=− 5– 2 IU/L, P=0.004) and ALT (median=− 2, IQR=− 7– 3 IU/L, P=0.0004) showed a significant decrease. Among 28 patients with ALT > 40 at baseline, reduction was significant both clinically (− 17, IQR=− 32–− 1) and statistically (P=0.0003). Total cholesterol levels (TC) increased (+13.4± 3.8 mg/dL, P=0.0006), as well as HDL-cholesterol (HDL-C) (+3.8± 1.2 mg/dL, P=0.02), LDL Cholesterol (LDL-C) (+7.6± 3.4, P=0.03) and glucose (+4.0± 1.8 mg/dL, P=0.02). D:A:D: and Framingham risk score did not change at 6 months after switch.Conclusion: A significant reduction of liver enzymes was observed after switching from TDF to TAF, especially in subjects with initial level of ALT > 40 IU/L. Glucose, TC, HDL-C, and LDL-C increased, with no effect on cardiovascular risk scores.Keywords: HIV, TDF, TAF, liver enzymes